Fundamental Analysis of Share Prices in Coal Mining Subsector Companies - Sri Rahayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research was conducted with the aim of proving the influence of fundamental factors on the share price of coal mining sub-sector companies listed on the Indonesia Stock Exchange with the accounting period of 2015-2019. The fundamental factors used in this study are the ratios used are Return on Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Earning Ratio (PER), and Price to Book Value (PBV). This type of research is quantitative descriptive which is associatively causal. Antitaif data is obtained from the company's annual report or financial statements that have been published on the Indonesia Stock Exchange. Sampling method is done by purposive sampling method. From the population of 27 coal mining sub-sector companies listed on the Indonesia Stock Exchange, 7 companies were taken as samples with 35 sample data. Hypothesis testing is done by panel data regression analysis method by first doing chow test, hausman test and lagrange multiplier test to choose a more appropriate model to use, and Random Effect Model (REM) is the more appropriate model to use in this study. The results of this study show that simultaneously Return on Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Equity Ratio (PER), and Price to Book Value (PBV) have a positive and significant effect on the share price of coal mining sub-sector companies listed on the Indonesia Stock Exchange. Partially EPS has a positive and significant effect on the share price of coal mining sub-sector companies. Partially ROA, PER, and PBV have no significant effect but give a positive direction to the share price of coal mining sub-sector companies. And partially DER has no significant effect and gives a negative direction to the share price of coal mining sub-sector companies listed on the Indonesia Stock Exchange.